Thin‐layer chromatography‐bioautographic method for the detection of arginase inhibitors. Issue 12 (26th April 2020) - Attia, Rym; Zedet, Andy; Bourjot, Mélanie; Skhiri, Eya; Messaoud, Chokri; Girard, Corine
Abstract: Arginase represents a promising therapeutic target for various pathologies including inflammatory, cardiovascular, and parasitic diseases or cancers. In the current work, we report, for the first time, about the development of a thin‐layer chromatography‐based bioautography which can be used to rapidly detect arginase inhibitors in complex matrices such as plant extracts. The assay is based on the detection of urea produced by arginase using the coloring reagent α‐isonitrosopropiophenone, resulting in the formation of a pink background on thin‐layer chromatography plates. The assay conditions were optimized in order to provide sufficient contrast between the pink colored thin‐layer chromatography plate and the clearer zones generated by the presence of arginase inhibitors. Different parameters were tested, such as incubation time and temperature, atmospheric conditions, as well as substrate and enzyme concentrations. This technique makes it possible to detect 0.1 μg of a known arginase inhibitor, N ω ‐hydroxy‐nor‐Arginine, after it has been spotted, either pure or mixed with a Myrtus communis methanolic fruit extract, and the plate has been developed in an appropriate solvent. The newly developed method was used to reveal the presence of an inhibitor in hempseed cakes ( Cannabis sativa L.).